Data capture and communication during transfers to definitive care in an inclusive trauma system. Issue 5 (May 2017) - Bradley, Nori L.; Garraway, Naisan; Bell, Nathaniel; Lakha, Nasira; Hameed, S. Morad
Abstract: Introduction: Background trauma survivors in rural areas transferred to urban centers have higher mortality than trauma patients admitted directly to urban centers. Transfer data in trauma registries is important for injury control. Prehospital and early physiologic data may reflect processes of pre-hospital care. British Columbia currently has no standardized process for trauma patient data transfer. Patients and methods: We performed a retrospective data analysis for major trauma patients (ISS >15) transferred to a Level I trauma center over a 1 year period (n = 243). Completion rates of paramedic form and ATLS primary survey variables were extracted. Nominal and interval descriptives were calculated. Documentation rates were considered deficient at <80% and severely deficient <60%. Odds ratios were calculated for primary facility data based on ISS ≥30 vs ISS <30, with 2-sided p-values for confidence intervals Results: Two hundred forty-three patients met inclusion criteria with a mean ISS of 26. Most injured patients were male (79%), the predominant mechanism was blunt (93%) and the average age at injury was 51 years old. Two hundred eighteen patients arrived by Emergency Health Services, and 140 (64%) of EHS pre-hospital forms were transferred with the patient chart. Pre-hospital airway, physiologic data, and GCS completion rates were severely deficient (43–49%). Primary facility data was adequately completed for airway management, systolic blood pressure, and heart rate in (80–83%). Completion rates were deficient for respiratory rate, GCS and temperature (60–77%). An ISS score ≥30 was significantly associated with a lower completion rate for GCS. Discussion and conclusion: Overall, documentation for inter-hospital transfer of major trauma patients in BC has significant deficiencies. Physiologic and basic ATLS variables are often omitted in transferred charts. The potential for adverse events is high but performance improvement is achievable. We recommend education, training and a standardized trauma transfer protocol to improve system-wide information transfer.